2020
DOI: 10.1111/1471-0528.16078
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell paracrine actions in tissue regeneration and potential therapeutic effect in human endometrium: a retrospective study

Abstract: Objective Determining genetic and paracrine mechanisms behind endometrial regeneration in Asherman's syndrome and endometrial atrophy (AS/EA) patients after autologous CD133+ bone marrow‐derived stem cell (CD133+BMDSC) transplantation. Design Retrospective study using human endometrial biopsies and mouse models. Setting Fundación‐IVI, IIS‐La Fe, Valencia, Spain. Samples Endometrial biopsies collected before and after CD133+BMDSC therapy, from eight women with AS/EA (NCT02144987) from the uterus of five mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…[3][4][5] Transplantation of UC-MSCs and BMSCs has demonstrated excellent therapeutic outcomes in IUA models and clinical studies. 18,19 However, UC-MSCs are allogeneic and have ethical limitations, and the invasive retrieval process of BMSCs is associated with an increased risk of pain and infection. In contrast, MenSCs may be more suitable for clinical applications, with the advantages of high cloning efficacy, non-invasive collection, ethical rationale, and immunomodulatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Transplantation of UC-MSCs and BMSCs has demonstrated excellent therapeutic outcomes in IUA models and clinical studies. 18,19 However, UC-MSCs are allogeneic and have ethical limitations, and the invasive retrieval process of BMSCs is associated with an increased risk of pain and infection. In contrast, MenSCs may be more suitable for clinical applications, with the advantages of high cloning efficacy, non-invasive collection, ethical rationale, and immunomodulatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…And the transplantation group also had a higher pregnancy rate compared with the non‐transplanted group (90% vs. 30%, p = 0.0225) (Alawadhi et al, 2014 ). Similarly, Cervello and collegues reported that human CD133 + BMDSCs, with intrauterine or tail vein injection in a murine model of EA, could engraft around the endometrial vessels and promote endometrial regeneration through paracrine actions (Cervello et al, 2015 ; de Miguel‐Gomez et al, 2020 ). These findings suggest that endometrial cells can be differentiated from donor BM cells, that is, stem cells from non‐endometrial sources can also participate in endometrial tissue regeneration.…”
Section: Progress and Challenges Of Endometrial Repair By Adult Stem Cellsmentioning
confidence: 95%
“…Besides, CD133 + BM-MSCs seem to activate several factors through a paracrine mechanism to help tissue regeneration, modifying endometrial behaviour through an immunomodulatory milieu that precedes proliferation and angiogenic processes. Insight into these processes could bring us one step closer to a non-invasive treatment for Asherman’s syndrome and endometrial atrophy (AS/EA) patients [ 78 ].…”
Section: Dpscs Regenerative Mechanism: Paracrine or Direct Differentiationmentioning
confidence: 99%